Water in peace operations: The case of Haiti. Issue 1 (14th April 2020) - Tignino, Mara; Irmakkesen, Öykü
Abstract : Protection of the environment in general, and water in particular, in relation to armed conflicts has gained increased attention in the last years. An area which should still be better analysed is the role of United Nations (UN) peace operations in relation to the protection of water. One of the most common objectives of these operations is the protection and promotion of human rights, including the right to water. In some instances, individuals have claimed the violation of human rights by UN forces and asked for remedies and compensation. This article first explores the inclusion of water in the mandates and practice of peace operations and builds on the human rights obligations of the UN as an international organization. It emphasizes the accountability of the UN through a comprehensive overview of the cholera epidemic in Haiti, demonstrating the undertakings with a view to engaging the responsibility of the organization.